Virtual Characters as a Low-Cost Solution to Boost Simulation Engagement: Beyond the Manikin. - Nold, Laura; Evans, MacKenzie; Grove, Traci R. (Nurse Educator, 2026)
This article focuses on a pilot project that explored the use of computer-generated 2-dimensional (2-D) virtual characters to enhance student engagement in prebriefing and debriefing during nursing simulation education. Conducted at a public Midwestern open-access university’s Bachelor of Science in Nursing program, the project introduced two characters—Micron Max, an infection preventionist, and Professional Polly, an ethics consultant—developed with free, open-access tools to support interactive learning. Survey results from participating students indicated that over 70% found the characters engaging, and qualitative analysis identified themes of increased engagement, improved learning and retention, interactivity, and multimodal support. While the characters showed promise in fostering student participation, limitations included their nonverbal 2-D format and the need for faculty familiarity with AI tools. The study suggests potential for broader integration of low-cost virtual characters in nursing education to enhance learner-centered simulation experiences.